CENTRAL MACULAR THICKNESS REDUCTION AFTER INTRAVITREAL INJECTION OF BEVACIZUMAB COMPARED TO INTRAVITREAL KETOROLAC IN NAIVE DIABETIC MACULAR EDEMA - Supanji Supanji; Angela Nurini Agni (International Journal of Retina, 2022)
Introduction: Diabetic macular edema (DME) is a debilitating complication of the diabetic eye. Vascular Endothelial Growth Factor (VEGF) was found to be responsible for this disease entity, and anti-VEGF remains the main treatment of DME. Inflammatory processes occur in diabetic eye, with some researchers postulates the role of them in the making of DME. This study’s objective is to search for anti-VEGF alternative using Non-Steroid Anti-Inflammatory Drugs (NSAID), ketorolac tromethamine. Methods: We conducted a double blind, randomized clinical trial in DME patients using intravitreal injection of bevacizumab and ketorolac. Central macular thickness (CMT) was assessed pre-treatment and one-month post-treatment. Best Corrected Visual Acuity (BCVA) and Intraocular Pressure (IOP) were also assessed. Wilcoxon tests were performed to evaluate changes in CMT, visual acuity, and IOP. Result: We enrolled 50 treatment-naïve DME patients from March 2020 to March 2021. Twenty-five patients were allocated for each group. There is a statistically significant difference in CMT at one-month follow-up between the two groups (p:0.001) and a markedly reduced CMT between the groups (p:0.001), with the reduction higher in bevacizumab group. BCVA changes significantly in bevacizumab group (p:0.01), but there is no statistically significant difference between the two groups (p:0.07). There’s a marked difference of IOP in 1 hour after injection in both groups, with higher transient IOP elevation in ketorolac group (p:0.02), but there is no marked difference in one-month follow-up (p:>0.05). The perceived pain right after intravitreal injection is not different between bevacizumab and ketorolac group. Conclusion: Intravitreal injection of ketorolac found to be inferior compared to bevacizumab in reducing CMT of DME. Meanwhile, there’s no differences in visual acuity, intraocular pressure (one-month follow-up) and pain after injection between two groups.